Pogostost neodzivnosti na aktivirani protein C pri bolnikih z vensko trombozo - Marinko, Tanja (Medicinski razgledi, 1997)
A group of 100 consecutive patients treated for deep vein thrombosis in the Trnovo Hospital of Intemal Medicine from January 1992 to December 1994, was studied for the presence of a new type of thrombophilia - resistance to activated protein C. There were 40 women and 60 men, aged 16 to 60 years (x=39). Primary deep vein thrombosis was established in 38 patients (18 % women, 82 % men), and secondary deep vein thrombosis in 62 patients (53 % women, 74 % men). Thirty-two per cent of patients had a positive family history; 79 per cent were treated for the first episode of deep vein thrombosis and the remainder for recurrent episodes. Resistance to activated protein C was determinated using a ratio between activated partial thromboplastin time with purified activated protein C and activated partial thro boplastin time without activated protein C. The lower normal limit was determined by measuring the activated protein C ratio in 100 sex and age matched healthy subjects (mean minus 2+- SD). Subjects with an activated protein C ratio less than 2,0 were considered resistant to activated protein C. Twenty patients were excluded from the study because of anticoagulant treatment, and 9 because of the presence of lupus anticoagulants. Activated protein C resistance was established in 10 (14 %) of the remaining 71 patients(6 women and 4 men). In the control group, the prevalence of activatedprotein C resistance was 3 per cent (3 men) (p < 0,05). One patient showed antithrombin III deficiency, and 2 patients protein C deficiency but none of them had activated protein C resistance. There were no association between activated protein C resistance and primary or secondary deep vein thrombosis, positive family history and first or recurrent episodes of the disease. The results of the study indicate that activated protein C resistanceis a frequent independent risk factor for deep vein thrombosis.
Keywords: Thrombophlebitis; venska tromboza; Etiology; neodzivnost; bolniki; Protein c; Physiology; Partial thromboplastin time